Ethics in end-of-life care: the first doula course in Italy - Alfano, Linda; Malcotti, Ivano; Ciliberti, Rosagemma (Medicina Historica, 2024)
Background: Although the role of the end-of-life doula is not yet officially recognized in Italy, the inaugural two-year training program organized in Genoa by the Genoese Society for Cremation (“So.Crem”) marks a significant step toward introducing this innovative and ethical approach aimed at humanizing the dying process.Methodology: Twenty participants in Italy’s first two-year end-of-life doula training program, conducted in Genoa by So.Crem, were recruited and interviewed. This qualitative research adopted a narratological approach, using thematic analysis for data processing.Objectives: To explore the ethical role of the end-of-life doula and examine how this figure contributes to a cultural shift in how death is experienced and addressed in society.Results:  The testimonies underline how the doula creates a space for deep listening and acceptance, offering an accompaniment that restores value and dignity to the dying person. The training, which integrates theory and practical experience, prepares students to support the person and the family in this delicate transition, promoting an ethical approach based on closeness and respect.Conclusions: The end-of-life doula emerges as a vital figure in promoting a cultural transformation that restores humanity and dignity to the dying process. This ethical practice challenges the prevailing tendencies toward detachment and distance increasingly observed in modern society. To enable this role to fully realize its potential, it is crucial to establish official recognition, including in Italy, to accredit its training, integrate its activities into care services, and enhance its effectiveness.